An iterative procedure to obtain inverse response functions for thick-target correction of measured charged-particle spectra - S. Pomp (2018)
A new method for correcting charged-particle spectra for thick-target effects is described. Starting with a trial function, inverse response functions are found by an iterative procedure. The variances corresponding to the measured spectrum are treated similarly and in parallel. Oscillations of the solution are avoided by rebinning the data to finer bins during a correction iteration and back to the original or wider binning after each iteration. This thick-target correction method has been used for data obtained with the MEDLEY facility at the The Svedberg Laboratory, Uppsala, Sweden, and is here presented in detail and demonstrated for two test cases. © 2006 Elsevier B.V. All rights reserved.